Dual-Band Integrated Antennas for DVB-T Receivers - Andrea D'alessandro; Roberto Caso; Marcos R. Pino; Paolo Nepa (International Journal of Antennas and Propagation)
An overview on compact Planar Inverted-F Antennas (PIFAs) that are suitable for monitor-equipped devices is presented. In particular, high efficiency PIFAs (without any dielectric layer) with a percentage bandwidth (%BW) greater than 59% (470–862 MHz DVB-T band) are considered. In this context, two PIFA configurations are reviewed, where a dual-band feature has been obtained, in the 3300–3800 MHz (14% percentage bandwidth) WiMAX and 2400–2484 MHz (2.7% percentage bandwidth) WLAN IEEE 802.11b,g frequency bands, respectively, to also guarantee web access to on-demand services. The two PIFAs fill an overall volume of  mm3 and  mm3, respectively. They are composed of a series of branches, properly dimensioned and separated to generate the required resonances. Finally, to show the extreme flexibility of the previous two configurations, a novel dual-band L-shape PIFA has been designed. A reflection coefficient less than −6 dB and −10 dB and an antenna gain of around 2 dBi and 6.3 dBi have been obtained in the 470–862 MHz DVB-T band and the 2400–2484 MHz WLAN band, respectively. The L-shape PIFA prototype can be obtained by properly cutting and folding a single metal sheet, thus resulting in a relatively low-cost and mechanically robust antenna configuration.